Negotiating success - Hornickel, Jim (John Wiley & Sons, Inc., 2014)
Negotiating Success provides expert guidance on how to improve strategies and outcomes in negotiating anything in professional and personal life. With a constant focus on the mind, body, and spirit of the professional negotiator, this easy-to- ready text brings a holistic approach to the hard and soft skills needed for ethical negotiations. The result is a better understanding of how to negotiate successfully for mutual benefit by all parties